Mineral composition, pedological characteristics and fractionation of selected chemical elements in soil of Maribor - Gaberšek, Martin; Grčman, Helena; Gosar, Mateja (Geologija, 2020)
The mineral composition, pedological characteristics and fractionation of selected chemical elements in the soil of Maribor were studied. The mineral composition reflects geological factors, especially the presence of igneous and metamorphic rocks in the surroundings of Maribor and in the Drava River catchment. Quartz prevails, followed by plagioclases, muscovite/illite, chlorite and dolomite. Potassium feldspar, amphiboles and calcite are also present in some samples. Relatively high pH values (6.9–7.4), high contents of plant-available phosphorous (13.5–185 mg/100 g of soil) and potassium in some samples reflect the anthropogenic influence on the pedological characteristics. The medians of the organic matter and carbonate contents are 8 % and 6.1 %, respectively. The majority of the samples belong to the sandy loam texture class, followed by loam class. Previous chemical analyses showed high contents of some potentially toxic elements (PTEs), especially Cu, Pb and Zn. We determined the fractionation of As, Cd, Co, Cr, Cu, Mn, Mo, Ni, Pb and Zn using a sequential extraction procedure. All PTEs, except Mn, are mostly bound to organic matter and residual fraction soluble in aqua regia, meaning that they are relatively strongly bound to soil components. Arsenic, Co, Cr and Ni are particularly strongly bound. The contents in the first and second stage, which represent the most easily exchangeable fractions of PTEs, are negligible. The results indicate that the contents of studied PTEs in the soil of Maribor do not pose an environmental threat.